Flow-batch analysis of clenbuterol based on analyte extraction on molecularly imprinted polymers coupled to an in-system chromogenic reaction. Application to human urine and milk substitute samples - Gonzalez, Natalia (2018)
A fully automated spectrophotometric method based on flow-batch analysis has been developed for the determination of clenbuterol including an on-line solid phase extraction using a molecularly imprinted polymer (MIP) as the sorbent. The molecularly imprinted solid phase extraction (MISPE) procedure allowed analyte extraction from complex matrices at low concentration levels and with high selectivity towards the analyte. The MISPE procedure was performed using a commercial MIP cartridge that was introduced into a guard column holder and integrated in the analyzer system. Optimized parameters included the volume of the sample, the type and volume of the conditioning and washing solutions, and the type and volume of the eluent. Quantification of clenbuterol was carried out by spectrophotometry after in-system post-elution analyte derivatization based on azo-coupling using N- (1-Naphthyl) ethylenediamine as the coupling agent to yield a red-colored compound with maximum absorbance at 500 nm. Both the chromogenic reaction and spectrophotometric detection were performed in a lab-made flow-batch mixing chamber that replaced the cuvette holder of the spectrophotometer. The calibration curve was linear in the 0.075–0.500 mg L−1 range with a correlation coefficient of 0.998. The precision of the proposed method was evaluated in terms of the relative standard deviation obtaining 1.1% and 3.0% for intra-day precision and inter-day precision, respectively. The detection limit was 0.021 mg L−1 and the sample throughput for the entire process was 3.4 h−1. The proposed method was applied for the determination of CLB in human urine and milk substitute samples obtaining recoveries values within a range of 94.0–100.0%.